Pengaruh Kebijakan Moneter Terhadap Kinerja Bisnis Perbankan Syariah - Asmaul Husna; Atika Atika; Syachrul Wahyudi; Andri Soemitra (Jurnal Riset AKuntansi dan Bisnis, 2021)
This paper is a literature review that aims to investigate the effect of monetary policy on the performance of Islamic banking. The methodology used is a review of previous studies both on a local Indonesian scale and on an international scale. The result, it was found that there are two classifications of the researchers views regarding this topic. The most of researchers conclude that monetary policy has negative effects on the performance of Islamic banking, while other conclude that monetary policy has no effect on the performance of Islamic banking. The basic thinking for this different findings can be referred to the classical opinion, that monetary policy is a "black box" that is influenced by the behavior of stakeholders, time lag, and changes in the strategy for formulating monetary policy transmission. Some suggestions found of this research is the claim that there is still a lack of sharia-based liquidity instruments that can be used as a valuable input for the monetary authorities.